Analisis Penerapan Cost Volume Profit (Cvp) Dalam Meningkatkan Laba Pada Usaha Gubuk Nenas (Studi Kasus Riset Kewirausahaan pada UMKM Gubuk Nenas di Desa Mendalo Darat) - Adam Al Fatah; Agus Syarif; Firmansyah Firmansyah (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
This Study aims to determine and analyze the costs incurred in the Gubuk Nenas business, see the movement of business productivity, and analyze the application of CVP to the business based on the movement of business costs and product sales. to see the application of the CVP method in the Gubuk Nenas Business through BEP and MOS calculations. The calculation involves costs, sales volume, and product selling prices. the method used in this study uses primary and secondary data derived from Gubuk Nenas business and literature. Based on the results of the CVP analysis, the BEP in the 2021 period for NassDrink products is IDR 23,196,008.88 with a BEP unit of 2,900 product units. And the MOS on NassDrink products is IDR.39,123,991.12 or with a percentage figure of 62.78% of total product sales in the 2021 period. Then the BEP on Nakrezz products is IDR 43,594,756.20 with a BEP unit of 2,906 product units. And the MOS on NassDrink products is Rp. 69,355,243.8 or with a percentage figure of 61.40% of total product sales in the 2021 period. Based on all the data, it is concluded that CVP Analysis can be applied to the Gubuk Nenas Business, so that it can determine the amount of product sales volume that must be achieved in the BEP and MOS. Gubuk Nenas business can achieve the profit targeted by the company. Planning can be made from price planning and cost planning which greatly affects the company's profit target achieved. In the cost planning section, the responsible party of the finance department should separate costs based on the total cost method which is separated into fixed costs and variable costs so that the separation will be more objective in planning